Improving Criminal Justice Students' Writing Outcomes Through Systematic Writing Instruction. Issue 4 (1st October 2016) - Odom, Stephanie; Helfers, Richard C.
Abstract : Criminal justice faculty members often express disappointment that their students are not meeting the writing expectations of the discipline. This study was a collaborative project between criminal justice and English faculty members to institute a writing pedagogy intervention to examine if criminal justice students' writing would improve over the course of a semester. Quantitative and qualitative methods were used to examine student attitudes toward writing, documentation style, grammatical correctness, academic diction, and paraphrasing/plagiarism. The results revealed statistically significant improvements in student writing when writing assignments were scaffolded and frequent feedback was provided. Additionally, this study used independent raters to compare student performance on papers from a previous semester, when minimal writing instruction was provided, to the papers from the current study. The results suggest the intervention may improve criminal justice student writing.